Design of Luminance-Chrominance Gain Equalizer Using Uniformly Distributed RC Circuits - Chutchavong, Vanvisa; Pirajnanchai, Virote; Doungpan, Satawat; Ngammongkolwong, Sudasawan; Rattanathanawan, Pongpan; Janchitrapongvej, Kanok (My University, 2024)
The propose of this paper is to design the luminance-chrominance gain equalizer use in the video waveform transmission. As it is known, the conventional measurement and gain corrector of chrominance distortion equipment is not so simple. This network corrector has to use fillers and delay time to separate the luminance signal and chrominance signal by means of low-pass and high-pass filter in connection. Here in, we deploy the uniformly distributed RC circuit (URC). We introduce two types of equalizers. The first type is to correct the luminance signal without deteriorating the chrominance signal. The second type is designed to correct the chrominance signal with no effect to luminance signal. Both equalizers comprise of a few gain amplifiers and URC circuits. From the simulation results, it is shown that the frequency response of gain equalizer given good effective in correcting video signal distortion. We also introduce the modulated sine-squared pulse test signal for measuring and correcting the amount of low gain and high gain of the chrominance signal.
Keywords: gain equalizer; luminance-chrominance signal; mod-sine-square pulse; test signal; URC circuit